Relationship of ergonomic stressors to birthweight and gestational age. - Marbury, M C (Scandinavian Journal of Work, Environment & Health, 1992)
Women in many occupations are exposed to ergonomic stressors (eg, prolonged standing, physical exertion, and long work weeks). After a consideration of the major methodological problems encountered in studying effects of ergonomic stressors on birthweight and gestational age, epidemiologic studies that have addressed this issue are reviewed. No individual ergonomic stressor has been consistently associated with effects on gestational age. However, most studies which have attempted to look at the cumulative effect of several stressors report that women in the highest exposure category are at higher risk of giving birth prematurely. In contrast, data regarding an association with birthweight are more variable, and firm conclusions cannot be drawn. While future studies that assess exposure to ergonomic stressors with a more comprehensive and quantitative approach are needed, current evidence is sufficient to suggest that clinicians should take ergonomic stressors into account in the assessment of their patients' risk for preterm delivery.